A Reusable Sensor for the Label‐Free Detection of Specific Oligonucleotides by Surface Plasmon Fluorescence Spectroscopy. Issue 1 (21st June 2013) - Nöll, Gilbert; Su, Qiang; Heidel, Björn; Yu, Yaming
<x xml:space="preserve">Abstract</x> The development of a reusable molecular beacon (MB)‐based sensor for the label‐free detection of specific oligonucleotides using surface plasmon fluorescence spectroscopy (SPFS) as the readout method is described. The MBs are chemisorbed at planar gold surfaces serving as fluorescence quenching units. Target oligonucleotides of 24 bases can be detected within a few minutes at high single‐mismatch discrimination rates. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>